Governance Of Community Nurses Participation In The Renal Care Center: A Document Review - Afzal, Ridha; Peristiowati, Yuly (Public Health and Safety International Journal, 2023)
The emergence of new regulations regarding the mandatory ownership of new Peritoneal Dialysis Units (PD Units) in regional hospitals in Indonesia creates new problems for PD patients after undergoing therapy. They need treatment by CAPD professionals who are still on the move. This study aims to discuss how far the community nurses are involved in the management of patient care in the PD unit so that an overview of their duties and functions is obtained in handling PD patients in the CAPD unit under management nursing. This document review used PRISMA analysis. Data were taken from Google Engine, with keywords: Peritoneal Dialysis, community nursing, and public health. Select documents from reputable journals for the last five years. The documents that were filtered (n=14) all met the search criteria for documents according to keywords. There were only two documents (n = 2) that raise the issue of community nurses and their role specifically in PD units in the community. The most discussed role was training (n=5). The challenges were bureaucracy or government regulations. This study recommended that community nurses could be empowered to care for PD patients after getting short CAPD training.